Pendampingan Digital Life Skills Menuju Kemandirian Ekonomi Untuk Komunitas Sahabat - Hendri Setyawan; Chrisna Suhendi (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The Sahabat Community is a supporter of the Dharma Bhakti Muslim Indonesia Foundation in Semarang, which consists of youngster man and women of productive age. They have great potential to become an economically independent generation as well as to become agents of change in their respective regions. Although not yet optimal, the Sahabat Community has initiated initiatives to empower the younger generation through short informal trainings as an effort to increase digital literacy. The FE UNISSULA community service team plans an optimization program for the digital literacy movement by sharpening the purpose of the activity in the form of digital life skills assistance. The program includes activities (i) assistance in the implementation of training to be more systematic with clear achievement targets and appropriate methods; (ii) providing training in the form of basic office applications and digital marketing (by BNSP certified instructors) as fundamental skills that are indispensable for both those who want to be entrepreneurs as well as employees; (iii) providing insight into the challenges and opportunities in the era of the digital revolution; (iv) providing motivation so that participants spread their enthusiasm and skills to other youth groups so that they can become agent of change in society.